Une perspective organisationnelle sur l’assurance : une explication du caractère conflictuel de la relation compagnie-agents par l’existence de l’inversion du cycle de production - Venard, Bertrand (Assurances)

(untitled) (HEC Montréal, 1993)
Relations between insurance companies and their distributors are regularly blemished with conflicts. An explanation of this phenomenon rests essentially in the existence of an inversion in the insurance product cycle. We demonstrate this by using a monograph on a French non-life insurance company.